GERAKAN PEMBERDAYAAN PEREMPUAN ISLAM: MUSLIMAT AL-WASHLIYAH DI SUMATERA TIMUR 1930-1945 - Faisal Riza (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
This article aims to unravel the history of the political movement Muslim women in East Sumatra in the early 20th century to show that the socio-religious identity of Muslim women have been forged through a number of socio-political, and show the different features of the relationship between Islam and women colonial period. This paper describes how the role Islam played in providing transformative power to fulfill the roles and develop the status of Muslim women in this area, is realized with the adoption of Islam such as hijab dress code, to provide education for them, organize themselves as an important means of political struggle of identity. Original argument in this study is that the new Islamic discourse is always born of a desire to challenge the conservative understanding of the role and status of women in different historical periods.